Analysis of Multiple Attempt Multipath Routing for mobile ad hoc networks. (19th March 2010) - Abbas, Ash Mohammad
In this paper, we analyse a routing protocol that identifies a maximal set of node-disjoint paths between a given source and a destination in multiple attempts using an approach that is a combination of a single-go routing protocol and an incremental protocol. We prove that doing so preserves the guarantee inherited from the incremental protocol to discover a maximal set of node-disjoint paths. In our analysis, we focus on the computational and communication overheads incurred in identifying node-disjoint paths and the time after which all routes identified are expected to fail.